IMPLEMENTASI PERATURAN DAERAH KABUPATEN BANYUWANGI NOMOR 6 TAHUN 2022 DALAM PROGRAM BANYUWANGI HIJAU (Studi Pada Dinas Lingkungan Hidup Kabupaten Banyuwangi) - Marini, Tasya Indah; Vitasari, Leni; Sudirman, Rio (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
Environmental issues, particularly waste management, have become major challenges in Banyuwangi Regency. Although Regional Regulation Number 6 of 2022 has been enacted and implemented through the Banyuwangi Hijau (BWH) Program, field practices show a lack of community participation, limited awareness of waste sorting, and delays in waste collection. This study aims to describe and analyze the implementation of the regional regulation using O’ Jones' theory, which includes three aspects: organization, interpretation, and application. This research employs a qualitative method with a descriptive approach. Data collection techniques include observation, in-depth interviews, and documentation with informants from the Environmental Agency and related community members. The results show that in terms of organization, the Environmental Agency has carried out its structure and duties relatively well, although there are still shortcomings in facilities and human resources. In terms of interpretation, socialization has been conducted but is not yet widespread, resulting in limited public understanding of the policy. In terms of application, implementation of the program remains suboptimal due to technical challenges and low public involvement. The study concludes that the implementation of Regional Regulation Number 6 of 2022 through the Banyuwangi Hijau Program has not been fully effective. Improved coordination among stakeholders, expanded public education, and enhanced operational systems are needed to achieve sustainable waste management.